Combined effect of packaging and pre-treatment with tiessa on the quality of ripened mangoes (C.V. carabao) under modified atmosphere storage - Dungganon, Jo Anne Granada
Postharvest life of ripened mangoes was extended for 12 days under Modified Atmosphere Storage using non-perforated and perforated pokyethylene bags as packaging.